Uso de técnicas cooperativas para mejorar el aprendizaje de funciones trigonométricas en los estudiantes de 2ºaño de bachillerato general unificado de la unidad educativa Fernando Suárez Palacio de la ciudad de Loja. Período 2015-2016 - Armijos Labanda, Mónica Janeth (2016)
The present investigation refers to the use of cooperative techniques learning to enhance the learning of trigonometric functions in the 2nd year students of General Unified Baccalaureate in the Unidad Educativa Fernando Suárez Palacio of Loja city. Period 2015-2016, for the study was made a diagnosis, in order to know the shortcomings and difficulties presented them, at time to learn trigonometric functions, thus leading to compliance with the following objective: seize the importance of cooperative techniques to improve learning of trigonometric functions 2nd year students of Unidad Educativa Fernando Suárez Palacio. The research responds to a descriptive and pre experimental design so that the following steps were apply: understanding, diagnosis, modeling, educational workshop and signs-ranges Wilcoxon's test. After applying the alternative, was concluded that cooperative learning techniques improve learning of trigonometric functions and were recommend the use of these techniques.